The legend of Mad Max [The complete saga from Mad Max to Furiosa] - Nathan, Ian (Palazzo Editions Ltd., 2024)
"The Legend of Mad Max is the ultimate guide to the high octane post-apocalyptic film series, directed by visionary filmmaker George Miller. This comprehensive history delves into the making of each film, exploring the unique vision and groundbreaking live action and special effects that have made Mad Max a cultural touchstone for over four decades. From the unforgettable characters and thrilling action sequences to the complex themes and deep mythology, this stunningly illustrated book provides an in-depth look at the world of the iconic road warrior, Mad Max. Buckle up and get ready for a wild ride through the wasteland as you discover the full story behind this classic film franchise. With detailed production information, behind-the-scenes stories, and stunning photography, The Legend of Mad Max is a must-read for fans of this celebrated series"--Publisher's description
"We acknowledge the Traditional Owners of the land on which these films were made. We pay our respects to their Elders, past and present, and the Aboriginal Elders of other communities." --Title page verso
Keywords: Mad Max beyond thunderdome; Mad Max II; Mad Max: Fury Road; Mad Max; Mad Max (Motion picture : 1979); Mad Max 2 (Motion picture); Mad Max beyond Thunderdome (Motion picture); Mad Max: fury road (Motion picture); Furiosa: a Mad Max saga (Motion picture); Mad Max films; Apocalyptic films / Australia; Apocalyptic films / Production and direction; Action and adventure films / Australia; Films d'aventures / Australie; Mad Max (Films); Films apocalyptiques / Australie; Bildband